Same topic, different genre: Elementary school children's mental representations of information embedded in narrative and expository texts. (August 2022) - Wannagat, Wienke; Steinicke, Valentina; Tibken, Catharina; Nieding, Gerhild
Abstract: Using a sentence recognition task, we investigated whether elementary school children's ( N  = 92; M age  = 9.3 years, SD  = 1.1 years) memory of the text surface, the textbase, and the situation model differed depending on whether the same information was embedded in an expository or a narrative text. Previous research with children that used narrative and expository texts dealing with different topics indicated beneficial effects narrative over expository texts regarding various indicators of processing on the levels of the textbase and the situation model. In contrast, our results did not indicate differences between narrative and expository texts for any of the levels of representation. Thus, the role of text topic in studies investigating the effect of genre on text comprehension should be investigated further. Highlights: We investigated whether children's text comprehension differed between genres. We created pairs of narrative and expository texts with the same topic. A sentence-recognition task indicated memory of three levels of representation. The results did not indicate differences between narrative and expository texts.